Optimising sports marketing strategy by the internet of things and blockchain technology. (15th May 2023) - Tang, Kun
The sports industry commercialises rapidly, transforming sports into special entertainment products on top of the traditional values. More entities engage in sports products and services to meet people's growing sports consumption needs. This exploration aims to meet people's sports consumption needs. First, the sports marketing theory is introduced alongside the concepts of the Internet of Things (IoT) platform and blockchain technology. Next, the sports marketing strategy is established based on the IoT platform + blockchain (Blockchain of Things (BoT)). Finally, the influencing factors of sports marketing strategy are analysed, and sports marketing strategy's influence is explored from the technical level. The results show that the current sports market reform has a superior cultural and legal environment.